Assessment of School Development Planning on the Implementation of Universal Basic Education Programme in Kwara State, Nigeria. - Omosidi, A. S.; Oyeniran, S.; Muritata, A. T. (NIU Journal of Humanities, 2017)
The study assessed school development planning on the implementation of universal basic education programme in Kwara State. School development planning is a part of school-based management committee aimed at making schools better places for pupils’ to learn by changing the way that schools work with their communities, the staff and the Local Government Education Authority (LGEA). The study covers the three senatorial district of Kwara State which comprises of Kwara Central, North and South. The study used descriptive survey method while stratified random sampling technique was used to select 150 out of 328 basic schools representing 45.7%. 150 Principals, 450 Vice Principals and 900 Teachers were used as subjects. One research instrument was used titled “Questionnaire on Implementation of School Development Planning in UBE Programme (QISDPUBE). The instrument was validated through face and content validities and 0.78 was obtained for its reliability. The five research questions raised in the study were analysed with percentage and average total counts. The findings of the study revealed that 64.8% of the respondents agreed that school environment was secure for pupils in the implementation of UBE programme. 59.8% of the participants also agreed that the classrooms are conducive for pupils learning for the implementation of UBE programme in the State. Finding also revealed that 66% of the respondents agreed that the school authority shared school management to achieve school goals in the implementation of UBE programme in Kwara State, while 64.1% of the respondents disagreed that teaching and learning resources are adequate for the pupils’ in the implementation of UBE programme in Kwara State and 67.3% agreed that teachers’ teaching effectiveness enhance pupils’ learning in the implementation of UBE programme in Kwara State. Based on the findings, it was recommended among others that no matter how small it is, a room should be located to serve as a library where teachers and pupils can have private reading and study, while relevant textbooks be provided to improve teaching and learning of teachers and pupils. Keywords : School Development Planning, School Environment, School Management, Teaching and Learning Resources, Universal Basic Education Programme.